Parent perspectives on consent for the linkage of data to evaluate vaccine safety: A randomised trial of opt-in and opt-out consent. (June 2013) - Berry, Jesia G; Ryan, Philip; Duszynski, Katherine M; Braunack-Mayer, Annette J; Carlson, Jillian; Xafis, Vicki; Gold, Michael S; ,
Background: We examined parents' consent preferences and understanding of an opt-in or opt-out invitation to participate in data linkage for post-marketing safety surveillance of childhood vaccines. Methods: A single-blind parallel-group randomised controlled trial: 1129 families of babies born at a South Australian hospital in 2009 were sent information at 6 weeks post-partum, explaining data linkage of childhood immunisation and hospital records for vaccine safety surveillance, with 4 weeks to opt in or opt out by reply form, telephone, or email. At 10 weeks post-partum, 1026 (91%) parents were followed up by telephone interview. Results: In both the opt-in (n = 564) and opt-out arms (n = 565), four-fifths of the parents recalled receiving the information (81% vs. 83%, P = 0.35), three-fifths reported reading it (63% vs. 67%, P = 0.11), but only two-fifths correctly identified the health records to be linked (43% vs. 39%, P = 0.21). Parents who actively consented (opted in) were more likely than those who passively consented (did not opt out) to recall the information (100% vs. 83%, P < 0.001), report reading it (94% vs. 67%, P < 0.001), and correctly identify the data sources (60% vs. 39%, P < 0.001). Most parents supported data linkage for vaccine safety surveillance (94%) and trusted its privacy protections (84%). Most parents wished to have minimal or no direct involvement, preferring either opt-out consent (40%) or no consent (30%). A quarter (24%) of parents indicated opt-in consent should be sought; of these, 8% requested consent prior to every use, 5% preferred to give broad consent just once and 11% preferred periodic renewal. Three-fifths of the parents gave higher priority to rapid vaccine safety surveillance (61%) rather than first seeking parental consent (21%), and one in seven was undecided (15%). Although 91% of parents reported that their babies were fully immunised (76%) or under-immunised (15%), and trusted vaccines as safe (90%), three-fifths (62%) were very or somewhat concerned about serious reactions. Limitations: The context of data linkage is limited to vaccine safety surveillance. Only recall and understanding retained at 1 month post enrolment were measured. Conclusions: This trial demonstrates that informed consent for a population-based surveillance programme cannot realistically be achieved using mail-based opt-in and opt-out approaches. While recall and understanding of the study's purpose were better among parents who actively consented (opted in) compared with parents who passively consented (did not opt out), participation was substantially lower (21% vs. 96% respectively). Most parents appeared to have a poor understanding of data linkage for vaccine safety surveillance; nonetheless, they supported data linkage. They preferred a system utilising opt-out consent or no consent to one using opt-in consent.